2020
DOI: 10.3390/ijerph17155576
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Effects of Executive Load on Perceived Exertion and Emotional Valence during Submaximal Cycling

Abstract: Endurance physical exercise is accompanied by subjective perceptions of exertion (reported perceived exertion, RPE), emotional valence, and arousal. These constructs have been hypothesized to serve as the basis for the exerciser to make decisions regarding when to stop, how to regulate pace, and whether or not to exercise again. In dual physical-cognitive tasks, the mental (executive) workload generated by the cognitive task has been shown to influence these perceptions, in ways that could also influence exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
6
1
Order By: Relevance
“…The experimental manipulations employed in the present study were insufficient to influence participants’ affective states (η p 2 = .03), though there was a trend toward negative affect for all conditions, as can be observed in Figure 3A. In a recent study conducted by Ávila-Gandía et al (2020), the authors investigated the extent to which highly demanding cognitive tasks performed concomitantly with exercise would influence participants’ perceived exertion and emotional states. The authors observed that higher executive loads were sufficient to upregulate perceived activation and evoke more negative affective responses than low demanding cognitive tasks.…”
Section: Discussionmentioning
confidence: 63%
“…The experimental manipulations employed in the present study were insufficient to influence participants’ affective states (η p 2 = .03), though there was a trend toward negative affect for all conditions, as can be observed in Figure 3A. In a recent study conducted by Ávila-Gandía et al (2020), the authors investigated the extent to which highly demanding cognitive tasks performed concomitantly with exercise would influence participants’ perceived exertion and emotional states. The authors observed that higher executive loads were sufficient to upregulate perceived activation and evoke more negative affective responses than low demanding cognitive tasks.…”
Section: Discussionmentioning
confidence: 63%
“…The present findings may align closer to a separation of these neural processes. Beyond effort, recent evidence has indicated that of greater importance may be the level of arousal and affective valence experienced by the load imposed on cognitive control (Ávila-Gandía et al, 2020). In the present study, demanding cognitive activity did not change affective experiences reported during the physical endurance task.…”
Section: Discussionmentioning
confidence: 99%
“…Other psychological processes, including affective valence, have been shown to be an important component of self-regulation during physical endurance performance (Hartman et al, 2019; Jones et al, 2015) and may help further understand the deleterious effect of a prior cognitively demanding task. For instance, Ávila-Gandía et al (2020) recently demonstrated that greater load on executive processes during prolonged physical performance was accompanied by increased arousal and less positive affective valence, but had little effect on the perception of effort during the physical task. In addition, the perception of effort has often been erroneously conflated, and used synonymously with the perception of fatigue (Borg, 1986; Halperin & Emanuel, 2020).…”
mentioning
confidence: 99%
“…While the factor for metrics of internal and/or external is very open and accepts different inputs, it will most likely be associated with assessments such as percentage of repetition maximum, distance covered in sprint, and other physically dominated parameters. However, this parameter of our model may as well incorporate the cognitive, decisional and emotional impact of load imposed on the athletes (Collins et al, 2018;Ávila-Gandía et al, 2020) and other related concepts. This makes the model customizable and adaptable to the coaches' training philosophy and can allow individual solutions to the athlete preparation puzzle.…”
Section: Discussionmentioning
confidence: 99%